EFFICACY AND LONG‐TERM CLINICAL OUTCOME OF COMORBID POSTTRAUMATIC STRESS DISORDER AND MAJOR DEPRESSIVE DISORDER AFTER ELECTROCONVULSIVE THERAPY. Issue 7 (10th November 2015) - Ahmadi, Naser; Moss, Lori; Simon, Edwin; Nemeroff, Charles B.; Atre‐Vaidya, Nutan
Abstract : Background: Many patients fulfill criteria for both posttraumatic stress disorder (PTSD) and major depressive disorder (MDD). Electroconvulsive therapy (ECT) is generally acknowledged to be the most‐effective treatment for refractory MDD. This study investigated the efficacy of ECT on long‐term clinical outcome of comorbid PTSD and MDD. Methods: This retrospective nested matched case‐control study is inclusive of 22, 164 subjects [3, 485 with comorbid MDD and PTSD (92 with ECT and 3, 393 without ECT) and 18, 679 without MDD and PTSD]. Results: Using the clinical global impression scale (CGI) to assess efficacy, more‐robust improvement of PTSD and MDD symptoms was observed with ECT (90%), compared to antidepressant‐treatment alone(50%) ( P = 0.001). During the median of 8 years of follow‐up, the death‐rate was 8% in subjects without PTSD and MDD, 9.7% in PTSD and MDD treated with ECT and 18% in PTSD and MDD without ECT ( P < 0.05). The suicide‐rate was 2.2 and 5.9% in PTSD and MDD with and without ECT‐treatment, respectively ( P < 0.05). Survival‐analyses revealed that the relative‐risk of cardiovascular and all‐cause mortality is not significantly different in patients with comorbid MDD and PTSD treated with ECT, compared to a matched‐cohort without PTSD and MDD ( P > 0.05). The relative risk of suicidality, all‐cause, and cardiovascular mortality was reduced 64, 65, and 46% in MDD and PTSD patients treated with ECT, compared to those without ECT ( P < 0.05). Conclusion: ECT is associated with a significant reduction of symptoms of PTSD and MDD, as well as reduction in risk of suicidality, cardiovascular, and all‐cause mortality in MDD and PTSD, an effect more robust than antidepressant‐therapy alone.